النظام الغذائي لسمك القرشScyliorhinus canicula (Linnaeus, 1758) (Scyliorhinidae: Elasmobranchii) ومؤشراته في المياه البحرية السورية - سعد أديب; علي مالك فارس; كرباج هيثم; جنيدي شادي (Latakia University Journal -Biological Sciences Series, 2014)
نفّذت هذه الدراسة على سمك قرش القط المنقط Scyliorhinus canicula (Linnaeus, 1758) في مياه السّاحل السّوري (الشاطئ الشرقي للبحر الأبيض المتوسط)، من رأس البسيط شمالاً حتى الحدود السورية اللبنانية جنوباً، بين درجتي عرض35° 55´ & 34° 50´ شمالاً، خلال الفترة الممتدة من كانون الثاني 2012 حتى أيلول 2013. تمّ جُمِعَ 417 فرداً (231 إناث، 186 ذكور)، على أعماق تتراوح بين 50-250 متر، من مناطق ذات قيعان رملية إلى رملية موحلة، بوسائل صيد مختلفة، أهمها الشرك فوق القاعي، سجلت أعلى كميات للمصيد خلال الربيع والصيف، وتراوحت الأطوال الكلّية للعينات بين 225 ملم – 515 ملم، وتراوحت أوزانها بين 22 – 380 غ. أظهر النّوع S. canicula تنوعاً في أنواع الفرائس التي يتغذّى عليها، إذ احتوى غذاؤه قشريات، أسماك عظمية، رخويات، صفائحيات غلاصم، ديدان، فضلاً عن بقايا فرائس لم تصنف. بلغ مؤشر فراغ المعدات 35.5 %، أتت القشريات بالمرتبة الأولى من حيث مؤشر الوجود (OI = 60.6)، وكانت مسيطرة بحسب مؤشر الأهمية النسبية (IRI = 5046.5)، ومفضلة بحسب معامل التغذية (QI = 1685.1). أما مجموعة الأسماك العظميّة فقد أتت بالدرجة الأولى من ناحية المؤشر الوزني (GI= 40.4%) وكانت مفضلة حسب معامل التغذية (QI = 917.3)، وأتت بالدرجة الثانية من حيث مؤشر الأهمية النسبية (IRI =1801.0)، بينما أتت الرخويات في المرتبة الثالثة وكانت مفضلة بحسب معامل التغذية، أما صفائحيات الغلاصم والديدان فكانت قليلة وحللت نتائجها ضمن مجموعة واحدة بالإضافة إلى الفرائس غير المصنفة وقد عدّت كفرائس عرضيّة. This study was performed on the small spotted catshark Scyliorhinus canicula (Linnaeus, 1758(, from Rass Albassit Northwards (35° 55́ N), down to the Syrian-Lebanese borders southwards (34° 50́ N) in the Eastern Levant of the Mediterranean sea during the period between January 2012 and September 2013. A total of 417 specimens (231 females, 186males) were collected at water depths 50-250m, from sandy or sandy-muddy bottoms by different fishing gears; mainly the sub-bottom hook. S. canicula suffers overfishing in the Syrian marine water. The highest capture quantity during this study was in spring and summer. The total length of specimens ranged from 225 to 515mm TL, and the weight from 22 to 380g. The results showed that Scyliorhinus canicula exhibited a diverse diet, and the preys belong to five taxonomical groups: Crustacea, Teleostei, Mollusca, Elasmobranchii, and Annelida as well as unidentified prey items. The vacuity index was 35.5%, where Crustaceans occupied the first degree, they were the dominant preys according to the Importance Relative Index (IRI = 5046.5), and preferable according to the dietary coefficient (QI = 1685.1). Teleostei came first according to the Gravimetric index (GI = 40.4 %), they were preferable according to the dietary coefficient (QI = 917.3), and second according to the Importance Relative Index (IRI = 1801.0). Mullosca were preferable and they were third. Elasmobranchii, Annelida, and the unidentified preys were classified as accidental prey items.